Diagnostic assessment of endothelial function in metabolic syndrome and coronary heart disease - V. A. Nevzorova; O. V. Nastradin; O. G. Pomogalova; E. S. Potapova (Кардиоваскулярная терапия и профилактика, 2011)
Aim. To study the endothelial status, endothelial relaxation and constriction reserve, inflammation markers, and adipokines in men with metabolic syndrome (MS) and various forms of coronary heart disease (CHD). Material and methods. In total, 236 male patients (mean age 56,5±2,07 years) were followed up. Serum levels of NO metabolites (NOnˉ), endothelin-1 (ET-1), and C-reactive protein (CRP) were measured, as well as the levels of cytokine system components (interleukin (IL) 6 and 10), tumor necrosis factor (TNF) alpha, and adipokines (leptin and adiponectin). Results. Endothelial dysfunction was manifested in reduced levels of NO metabolites in MS and additional increase of serum ET-1 concentration in CHD. Serum CRP levels were increased in MS and CHD, being maximal in patients with Q-wave myocardial infarction (MI). In MI patients, the levels of TNF-alpha and IL-10 were decreased, while IL-6 concentration was elevated. Leptin concentration was increased in participants with MS only, or the combination of MI and MS. Adiponectin levels were decreased in MI patients, regardless of MS presence or absence. Conclusion. The combination of MS and CHD was characterised by endothelial dysfunction. Serum inflammatory activity (increased CRP levels) was elevated in MS and was maximal in Q-wave MI. Serum levels of adipokines were dependent on MS presence or absence, with increased leptin concentration both at the risk factor stage and the Q-wave MI stage.